Long Non-Coding RNA SNHG14 Contributes to the Development of Hepatocellular Carcinoma via Sponging miR-217 - Xu, Xiaoyong (Onco Targets Ther, 2020)
BACKGROUND: Thousands of long non-coding RNAs (lncRNAs) have been functionally verified as crucial regulators of physiological processes and disease progressions, yet their roles in hepatocellular carcinoma (HCC) have not been clearly illuminated. METHODS: We analyzed the expression of lncRNA-SNHG14 in TCGA data via bioinformatic analysis and detected its expression in HCC specimens by reverse transcription‐quantitative polymerase chain reaction (RT‐qPCR). Loss-of-function experiments were used to study the biological function of SNHG14 in HCC cells. RT-qPCR, Western blotting and dual-luciferase reporter assay were carried out to investigate the molecular mechanism of SNHG14 in HCC. RESULTS: The upregulation of lncRNA-SNHG14 was observed in HCC tissues compared with normal tissues via RT-qPCR and bioinformatic analysis of TCGA data. Silencing of SNHG14 inhibited cell proliferation and induced cell apoptosis in HCC cells. microRNA-217 (miR-217), the tumor-suppressive miRNA in HCC, was predicted and confirmed as a miRNA sponged by SNHG14 in HCC cells. Via downregulation of miR-217, SNHG14 increased the expression of several miR-217-related oncogenes and subsequently activated oncogene-related signaling pathways in HCC cells. In addition, inhibition of miR-217 reversed SNHG14 silencing induced decrease of cell proliferation and increase of cell apoptosis. Their association was verified in the published microarray dataset and the collected HCC samples. CONCLUSION: In summary, SNHG14 is involved in the development of HCC via sponging miR-217 and it may be a biomarker for patients with HCC.